Walter Benjamin e o tempo da grande industria - Eide Sandra Azevedo Abrêu (Dialogos, 2017)
Este artigo procura levantar, através de textos de Walter Benjamin escritos na década de 1930, dimensões da reflexão sobre a "era da grande indústria". Os resultados indicam que Benjamin teria adotado uma postura simultaneamente pesarosa e esperançosa diante da perda de experiência que enxergou nesse tempo histórico.ABSTRACT. This article is a survey of Walter Benjamin’s reflections on the age of the great industry through his writings of the 1930’s. The results indicate that Benjamin had a simultaneous regretful and hopeful stance regarding the loss of experience observed in that historical period.